Resilience as a moderator in the relationship between burnout and subjective well-being among medical workers in Serbia during the COVID-19 pandemic - Safiye, Teodora; Vukčević , Branimir; Čabarkapa, Milanko (Vojnosanitetski pregled, 2021)
Background/Aim. During the ongoing COVID-19 pandemic, exhaustion and difficulties at work can seriously endanger the mental health of medical workers. The aim of this study was to examine whether resilience is a moderator of the association between burnout and subjective well-being among medical workers at the time of the pandemic. Methods. The research was conducted on a sample of 521 medical workers (354 female), among whom were 245 physicians and 276 medical technicians. The average age of the respondents was 38.66 years. Data were collected using online questionnaires comprising the Brief Resilience Scale, the Work Burnout Scale, the Short Subjective Well-being Scale, and the Sociodemographic Data Questionnaire. Regression and interaction analysis (by SPSS macro ''PROCESS 3.5'') was used for data analysis and processing. Results. The results showed that burnout was a significant negative predictor of subjective well-being of medical workers (ß = -0.19; p < 0.01) and a significant positive predictor of subjective well-being (ß = 0.40; p < 0.01), as well as that the interaction of resilience and burnout was a significant positive predictor of subjective well-being (ß = 0.09; p < 0.01). In subjects who had developed resilience at the level of +1 standard deviation (SD), the negative effect of burnout on subjective well-being was 2.8 times lower than in subjects who had resilience at the level of -1 SD. Conclusion. The study confirmed that resilience reduces the negative connection between burnout and subjective well-being, which is a significant argument that medical workers should be provided with resilience training programs to prevent burnout and preserve mental health during a pandemic.
Keywords: covid-19; resilience, psychological; burnout, professional; quality of life; medical staff; occupational exposure; surveys and questionnaires